Prenatal stress and affective disorders in a population birth cohort. (29th November 2012) - Kleinhaus, Karine; Harlap, Susan; Perrin, Mary; Manor, Orly; Margalit‐Calderon, Ronit; Opler, Mark; Friedlander, Yehiel; Malaspina, Dolores
Abstract : Kleinhaus K, Harlap S, Perrin M, Manor O, Margalit‐Calderon R, Opler M, Friedlander Y, Malaspina D. Prenatal stress and affective disorders in a population birth cohort.  Bipolar Disord 2012: 00: 000–000. © 2012 John Wiley & Sons A/S.Published by Blackwell Publishing Ltd. Objectives:  Pregnant women exposed to an acute traumatic event are thought to produce offspring with an increased incidence of affective disorders. It is not known whether there are specific times in pregnancy which confer increased vulnerability, or if psychosocial stress alone can increase the incidence of affective disorders in offspring. We examined the relationship of the timing of an acute psychosocial threat during pregnancy to the incidence of affective disorders in offspring using data from a large birth cohort. Methods:  Using data on 90079 offspring born in Jerusalem in 1964–1976 and linked to Israel's psychiatric registry, we constructed proportional hazards models to evaluate the link between gestational age during the Arab–Israeli war of June 1967 and incidence of mood disorders. Results:  Those in their first trimester of fetal development during the war were more likely to be admitted to hospitals for any mood disorders [relative risk (RR) = 3.01, 95% confidence interval (CI): 1.68–5.39, p = 0.0002]; for bipolar disorder the risk was doubled (RR = 2.44, 95% CI: 0.996–5.99, p = 0.054) and for all 'other' mood disorders the risk was tripled (RR = 3.61, 95% CI: 1.68–7.80, p = 0.001). Mood disorders were also increased in offspring whose mothers had been in the third month of pregnancy in June of 1967 (RR = 5.54, 95% CI: 2.73–11.24, p < 0.0001). Conclusions:  A time‐limited exposure to a severe threat during early gestation may be associated with an increased incidence of affective disorders in offspring. The third month of fetal development was a moment of special vulnerability.